2006
DOI: 10.1007/s11274-005-9094-0
|View full text |Cite
|
Sign up to set email alerts
|

Flavonoids and Growth Hormones Influence Endophytic Colonization and in Planta Nitrogen Fixation by a Diazotrophic Serratia sp. in Rice

Abstract: Several endophytic diazotrophs were isolated from cultivars of rice and screened for their diazotrophy by nitrogenase assay and amplification of partial nifH gene. Ability of one of the diazotrophic endophytes, Serratia sp. (isolate EDA2 from cultivar ADT36) to colonize the rice seedlings grown in the presence of flavonoids and growth hormones, under gnotobiotic condition was assessed in cultivar ADT36 using a strain marked with transposonbased egfp and Km r . The endophytic colonization was monitored through … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
24
0
4

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
3
2

Relationship

0
10

Authors

Journals

citations
Cited by 52 publications
(29 citation statements)
references
References 22 publications
1
24
0
4
Order By: Relevance
“…Flavonoids can also stimulate endophytic colonization of rice by Serratia spp. (Balachandar et al, 2006) and colonization of Arabidopsis thaliana by Herbaspirillum seropedicae (Gough et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Flavonoids can also stimulate endophytic colonization of rice by Serratia spp. (Balachandar et al, 2006) and colonization of Arabidopsis thaliana by Herbaspirillum seropedicae (Gough et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…Numerous studies have characterized bacterial diversity in scores of plants, and have reported that the bacterial endophyte community can be specific to particular species of host plants and even cultivars (Sturz et al, 1997;Adams & Kloepper, 2002;Araujo et al, 2002;Zinniel et al, 2002;Rasche et al, 2006;Sun et al, 2008). The composition of root exudates is thought to play a central role in recruiting bacteria from the bulk soil into the rhizosphere (Bais et al, 2006;Hartmann et al, 2009;Micallef et al, 2009) and, finally, into the endosphere (Balachandar et al, 2006), but little is known about specific plant genes that facilitate the recognition and selection of endophytic bacteria.…”
Section: Introductionmentioning
confidence: 99%
“…Plants also play an important role in establishing this interaction since they produce compounds that affect their associations with microorganisms. One of such compounds is naringenin, a flavonoid produced as secondary metabolite, that can stimulate or inhibit specific genetic responses in different bacteria associated with plants [14,15]. It was demonstrated that naringenin stimulates the endophytic colonization of Arabidopsis thaliana by H. seropedicae Z67 [16].…”
mentioning
confidence: 99%